Problem Profile of Drugs (DRPs) in Antidiabetic Therapy for Type 2 Diabetes Mellitus Patients in The Inpatient Ward - Alfhina, Luluk; Harahap, Herpan Syafii; Alaydrus, Raisya Hasina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The occurrence of type 2 diabetes mellitus keeps rising worldwide each year, and this includes Indonesia. Individuals with type 2 diabetes mellitus frequently encounter Drug-Related Problems (DRPs) due to multiple medications resulting from related health issues. Thus, recognizing DRPs is essential to enhance treatment success. The Mataram City Regional General Hospital stands out as one of the hospitals with the most significant number of type 2 diabetes mellitus cases each year from 2021 to 2023, showing an increase of 18.81%. The objective of this study was to analyze the profile of DRPs (Drug-Related Problems) in antidiabetic therapy among type 2 diabetes mellitus patients in the inpatient ward of Mataram City General Hospital during the period of April 2025. Data gathering was performed retrospectively by reviewing medical documents and conducting patient interviews. The medical documents were examined using the Cipolle classification, and the findings were illustrated in a diagram format with Microsoft Excel. The findings indicated that drug-related issues (DRPs) were present in hospitalized patients with type 2 diabetes mellitus at the Mataram City Regional General Hospital in April 2025. Among the 55 diabetes patients, 7 were found to have DRPs (12.72%), with DRPs manifesting as indications lacking medication (9.09%) and medications prescribed without indications (3.64%).